Efecto de diferentes dosis e interaccion de reguladores de crecimiento en el rendimiento del frijol (Phaseolus vulgaris) variedad Porrillo Sintetico - Álvarez S, E. (International Center for Tropical Agriculture, 1976)
An expt was conducted at CIAT to determine the effect of the application of 5, 10 or 15 ppm NAA, GA and BAP, alone or in combination, on yield and its components. Data were taken on time of emergence, flowering, fruiting, physiological maturity and harvest. Among the growth regulators applied, no synergistic effect on yield was found. To increase yield with NAA, much higher rates (up to 300 ppm) would have to be considered. GA had a notable effect on increasing vegetative development. Delay in leaf senescence apparently affected seed size (increased). Some of the treatments delayed physiological maturity. (CIAT)